OPERATIONAL SUSTAINABLE PERFORMANCE AND TAX AVOIDANCE: EVIDENCE FROM INDONESIA - Indah Umiyati; Trisandi Eka Putri; Mala Septiana Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
Tax is one of the main sources of state revenue imposed on the people based on the applicable law. In practice, problems related to tax collection in Indonesia often occur, one of which is the practice of tax avoidance by companies by exploiting loopholes in tax regulations. One of the factors suspected to be related to tax avoidance is sustainability performance. This study aims to analyze the relationship between OSP and tax avoidance in companies listed on the Indonesia Stock Exchange for the energy, consumer non-cyclicals and consumer cyclicals sectors. This research analyzes companies in the energy sector, consumer non-cyclicals and consumer cyclicals from 2019-2021 and obtained a sample of 106 company-years. To control company characteristics and governance factors that can affect tax evasion, the study used control variables for firm size and institutional ownership. Estimation is done by the OLS method. The results of the study show that operational sustainability performance has a negative effect on tax evasion. This shows that the operational dimension of sustainability performance results from a sense of corporate responsibility to stakeholders, so that the better the operational sustainability performance indicates the better the company's responsibility to stakeholders, including in terms of paying taxes. Under these conditions, companies will be more obedient in paying taxes and minimize tax evasion efforts